Visualization of oral function during playing a wind instrument by a lateral dental impression: a proof-of-concept investigation - Hattori, Mariko; Tanabe, Gen; Patzelt, Sebastian B. M.; Schulze, Dirk; Sumita, Yuka I.; Wakabayashi, Noriyuki (Frontiers in Oral Health, 2025)
Embouchure describes the interaction of the teeth, lips, tongue, buccal mucosa, and surrounding muscles when playing woodwind and brass instruments. In dental practice, impression material is used to capture the oral structure and function. In this proof-of-concept investigation, embouchure was examined using a silicone-based dental impression material. The participants were 1 oboe player, 1 alto saxophone player, and 4 tenor saxophone players. Four of the participants were amateurs and 2 were professionals. The dental impression material was mixed and inserted onto the buccal aspect of the upper molars. The musicians blew test tones and maintained embouchure for 30 s while a lateral embouchure impression was taken. The hardened material was removed and scanned using cone-beam computed tomography. The three-dimensional surface data of the impression were exported, and the mean thickness was analyzed. The impressions showed the space between the alveolar and buccal mucosae. The mean thickness ± standard deviation of the impressions was 2.35 ± 0.85 mm. The oboist showed the smallest thickness, while the tenor saxophonists showed the greatest thickness. The method enabled visualization of the unique morphology of each participant. The results suggest that embouchure can be objectively evaluated using the presented technique. Making embouchure impressions to assess oral problems should enable dentists to evaluate changes in music playing resulting from oral problems or for their treatment. Further studies in a larger population are needed to generalize the results.